The state's obligation to protect highly migratory species according to the 1982 law of the sea convention - Hilda, Hilda; Asriyani, Asriyani (Tomini Journal of Aquatic Science, 2022)
Highly Migratory Species are one of the fish resources legally protected according to the UNCLOS 1982. This protection is carried out to ensure adequate world fish stocks and the sustainability of these fish resources. Internationally, the efforts to protect it are the obligation of all countries. This study examines the state's commitment to preserving these Highly Migratory Species. This research is normative juridical research that utilizes secondary data, including primary, secondary, and tertiary legal materials using qualitative analysis. The study results show that several international legal instruments complement the provisions of the UNCLOS 1982, which regulates the state's obligations to protect Highly Migratory Species in a concrete way, i.e., related to management and conservation. Some regional fisheries organizations have been formed to implement the state's obligation to cooperate in managing and protecting Highly Migratory Species in each specific regulated area.